The Workers of Northeast Chubut (Patagonia, Argentina): A Study of the Contextual Features that Shaped the Formation of a Working - Class Fraction - Perez Alvarez, Gonzalo Gabriel (2015)
We are interested in deepening the knowledge about the history of the working class in the Patagonia in general and in Chubut´s North-East especially. In this region, from the decade of sixty, there was stimulated the conformation of an industrialization subsidized by the national and provincial State, which gave origin to Trelew´s Industrial Textile Park and to the producing plant of primary aluminium, ALUAR, in Puerto Madryn. Through these years there conforms in the region a new working class, product of the massive arrival of different quotas immigrants, already be from other provinces of the country, from the rural zones of the province of Chubut and from the neighboring country of Chile. This working class, extremely heterogeneous and that in many cases was not bringing experiences of industrial work, union activity or up to of urban life, meets a social context of full employment, frequent inauguration of new factories and the possibility to improve his living conditions in the frame of obtain better conditions of work. We try to understand how this working class conforms, how develop his first actions and his organization, and in what conditions they found with the changes that begin about the middle of eighty and that impacted her squarely during the nineties. For the characteristics of what we seek study it had been non-conducive work only with written sources, because they only let us see a part of the process. These sources say little on the processes of development of organizations, the conformation of working militants, his transformations and debates. So was crucial the contribution of oral sources, as it provides key elements to approach the meaning of those facts had for the subjects who developed them. In this article we wonder specifically about the characteristics of the formation of a working class fraction in a region of the country in the frame of a subsidized industrialization.